Natural History of Paratelmatobius gaigeae (Amphibia, Anura, Leptodactylidae): Description of the Tadpole and Advertisement Call - Domenico, Eleonora A.; Haddad, Celio F. B. [UNESP]; Zaher, Hussam (Soc Study Amphibians Reptiles, 2014)
The genus Paratelmatobius includes species that are usually rare and with limited distribution. As a result, data on natural history and larval morphology are still relatively scarce for some species. Here, we describe the tadpole of Paratelmatobius gaigeae and provide data on the reproductive biology and vocalization of the species. Both ecological and morphological features of the tadpole of P. gaigeae are similar to other tadpoles of the genus. The tadpole of P. gaigeae belongs to the exotrophic and benthic guild, with an anteroventral mouth, dorsally located eyes, identical dental formulae to the other species of the genus, and a large gap without papillae on the rostral portion of the anterior labium. The advertisement call is very short, pulsed, and consisting of single notes.